Effectiveness of mediation and conciliation in extrajudicial services as an effective means in resolution of disputes - Sá , Alexander Rolim; De Negreiros , André Bruno Façanha; Monteiro, Maria Darlene Braga Araújo; Lima, Elke Castelo Branco (Seven Editora, 2023)
The present work has as its theme "Effectiveness of mediation and conciliation in extrajudicial services as an effective means of resolving disputes". During the work, mediation and conciliation were presented as effective tools and alternatives in dispute resolution. Therefore, in the course of this monographic work, certain questions are answered, such as: How is the right to citizenship and the guarantee of access to justice implemented in Brazil? What is the performance of extrajudicial services for dejudicialization? For the elaboration of this work, a study will be carried out through bibliographical, scientific and documentary research, in addition to disposing of the doctrines of Caio Cesar Vieira Rocha (2017), Carlos Alberto de Salles (2020), Fernanda Tartuce (2018), Fabiana Marion Spengler (2013). Finally, it is concluded that mediation and conciliation are currently considered by many to be the "key/tool" to open new doors to justice in Brazil, especially during the Covid-19 pandemic. Furthermore, with advances in the use of new technologies and information, fundamental changes are needed, particularly with regard to access to justice. It also concludes that justice cannot be stopped and that citizenship does not consist only in political messages in favor of individual rights, but also in the State’s obligation to provide minimum conditions for the exercise of that right. DOI: https://doi.org/10.56238/methofocusinterv1-021